Grape Seed Proanthocyanidin Extract Ameliorates Diabetic Bladder Dysfunction via the Activation of the Nrf2 Pathway - Chen, Shouzhen; Zhu, Yaofeng; Liu, Zhifeng; Gao, Zhaoyun; Li, Baoying; Zhang, Dongqing; Zhang, Zhaocun; Jiang, Xuewen; Liu, Zhengfang; Meng, Lingquan; Yang, Yue; Shi, Benkang (PloS one, 2015)
Diabetes Mellitus (DM)-induced bladder dysfunction is predominantly due to the long-term oxidative stress caused by hyperglycemia. Grape seed proanthocyanidin extract (GSPE) has been reported to possess a broad spectrum of pharmacological and therapeutic properties against oxidative stress. However, its protective effects against diabetic bladder dysfunction have not been clarified. This study focuses on the effects of GSPE on bladder dysfunction in diabetic rats induced by streptozotocin. After 8 weeks of GSPE administration, the bladder function of the diabetic rats was improved significantly, as indicated by both urodynamics analysis and histopathological manifestation. Moreover, the disordered activities of antioxidant enzymes (SOD and GSH-Px) and abnormal oxidative stress levels were partly reversed by treatment with GSPE. Furthermore, the level of apoptosis in the bladder caused by DM was decreased following the administration of GSPE according to the Terminal Deoxynucleotidyl Transferase (TdT)-mediated dUTP Nick-End Labeling (TUNEL) assay. Additionally, GSPE affected the expression of apoptosis-related proteins such as Bax, Bcl-2 and cleaved caspase-3. Furthermore, GSPE showed neuroprotective effects on the bladder of diabetic rats, as shown by the increased expression of nerve growth factor (NGF) and decreased expression of the precursor of nerve growth factor (proNGF). GSPE also activated nuclear erythroid2-related factor2 (Nrf2), which is a key antioxidative transcription factor, with the concomitant elevation of downstream hemeoxygenase-1 (HO-1). These findings suggested that GSPE could ameliorate diabetic bladder dysfunction and decrease the apoptosis of the bladder in diabetic rats, a finding that may be associated with its antioxidant activity and ability to activate the Nrf2 defense pathway.